Activated Carbon and Biochar Derived from Sargassum sp. Applied in Polyurethane-Based Materials Development - Julie Mallouhi; Varga Miklós; Sikora Emőke; Gráczer Kitty; Bánhidi Olivér; Sarra Gaspard; Francesca Goudou; Viskolcz Béla; Szőri-Dorogházi Emma; Bela Fiser; Фішер Бейло; Fiser Béla (MDPI, 2024)
Abstract. Activated carbon (AC) and biochar (BC) are porous materials with large surface areas and widely used in environmental and industrial applications. In this study, different types of AC and BC samples were produced from Sargassum sp. by a chemical activation and pyrolysis process and compared to commercial activated carbon samples. All samples were characterized using various techniques to understand their structure and functionalities. The metal content of the samples was characterized by using an inductively coupled optical emission spectrometer (ICP-OES). A toxicity test was applied to investigate the effect of AC/BC on organisms, where Sinapis alba seed and Escherichia coli bacteria-based toxicity tests were used. The results revealed that the samples did not negatively affect these two organisms. Thus, it is safe to use them in various applications. Therefore, the samples were tested as fillers in polyurethane composites and, thus, polyurethane-AC/BC samples were prepared. The amounts of AC/BC mixed into the polyurethane formulation were 1%, 2%, and 3%. Mechanical and acoustic properties of these composites were analyzed, showing that by adding the AC/BC to the system an increase in the compression strength for all the samples was achieved. A similar effect of the AC/BC was noticed in the acoustic measurements, where adding AC/BC enhanced the sound adsorption coefficient (α) for all composite materials.
https://www.mdpi.com/2073-4360/16/20/2914
Editorial Board: https://www.mdpi.com/journal/polymers/editors
Contents: https://www.mdpi.com/2073-4360/16/20
Keywords: polyurethane; polymer composite; acoustic properties; toxicity test